Dimensions of the artistic image in Rashid's poetry Nasser Hussein (Journal of the College of Basic Education, 2022)
The world of poetry is the world of fertile imagination that breaks the collar of reality to spark salesexpressive and creative spaces; breaks space and time; And launch into the world of creativity artistic imagescolored with the feather of inspiration; So you look at reality from angles far from the tangible and the tangible. angles crossAbout the poet's ability to find new pictorial charges that link the vocabulary knot in a visual atmosphereNew, the image is an important pillar of the artistic construction of the poem; And an important methodexpression; It is the mirror through which the poet tries to portray everything that waves his inner worldColorful and different feelings and sensations float on the body of the poetic text throughlanguage formations; that provide us with vivid and vibrant images; So that it seems to the reader of the poem as ifHe does not know ((Is he reading the written poem or witnessing a scene from the scenes of existence))!